Symmetrical Dimethylarginine as a Diagnostic Parameter in Hermann's Tortoises (Testudo hermanni) - Lehmann, Verena; Altherr, Barblin; Pantchev, Nikola; Öfner, Sabine; Zablotski, Yury; Murphy, Rachel; Coyne, Michael; Kölle, Petra (Frontiers in Veterinary Science, 2022)
Background: Despite improvements in habitational conditions, kidney disease is relatively common in tortoises. Objectives: Purpose of this study was the establishment of Symmetrical dimethylarginine (SDMA) reference values for clinically healthy Hermann´s Tortoises. Animals: Clinically healthy Hermann´s Tortoises (n = 131) were included in the period from October 2017 to September 2019. Methods: Creatinine and other biomarkers were tested at IDEXX Laboratories, Germany using residual blood samples from Hermann`s tortoises. SDMA was measured with the IDEXX test and verified byliquid chromatography-mass spectrometry at IDEXX Laboratories, USA. Results: SDMA values ranged from 1 21 µg/dl (n = 131) for the IDEXX SDMA Test and SDMA values ranged from 1 17 µg/dl (n = 82) for LC-MS. For the comparison of the two measuring systems, the following results were obtained R2 = 0.75 (p < 0.001). Conclusion and Clinical Importance: SDMA can be measured in Hermann´s Tortoises and the reference values range in clinically healthy animals is comparable to that of dogs and cats.